The Impact of Tourism on the Quality of Life of Communities in Tourist Destination Areas: A Systematic Review - Nopiyani, Ni Made Sri; Wirawan, I Md Ady (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Tourism development can have a positive or negative impact on the lives of local communities. AIM: This systematic review aims to determine the impact of tourism on the quality of life (QoL) of people in tourist destination areas. METHODS: The search was conducted on the Science Direct database, Taylor Francis, EBSCO Host, Wiley Online Library, and Google Scholar. The keywords used were “residents’ QoL” AND impacts of tourism. Inclusion criteria were articles that focus on the QoL of people in tourist destination areas, published from 2015 to 2019 in peer-reviewed journals, in English. Articles were excluded if they were qualitative studies, literature reviews, and if full papers were unavailable. The review was conducted on 18 articles selected from 673 articles obtained in the initial search. RESULTS: Tourism has an impact on the QoL of local communities. In general, the domains that are perceived as being positively affected are the improvement of the economy, employment opportunities, community pride, cultural exchanges, and increased facilities availability. Meanwhile, the domains that are negatively affected in most of the studies are health, safety, quality of the physical environment, cost of living, accessibility to public facilities, and social relations. Apart from that, there is also dissatisfaction with the types of jobs available and the low level of community involvement in tourism development. CONCLUSIONS: Tourism can have both positive and negative impacts on the QoL of local communities. Efforts to minimize the negative impacts of tourism should be undertaken to improve community support for tourism development.